1984
DOI: 10.1002/pd.1970040308
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maternal serum alpha‐fetoprotein levels associated with intrauterine genetic diagnostic procedures

Abstract: The amount of fetal-maternal transfusion during invasive intrauterine diagnostic instrumentation was determined by measuring the increase in maternal serum alpha-fetoprotein (delta AFP) caused by the procedure. Fetal liver biopsy or fetoscopy for purposes other than blood sampling caused a mean delta AFP of 11.4 ng/ml and 34.2 ng/ml, respectively. Fetoscopy with fetal blood sampling produced a mean delta AFP of 211.8 ng/ml, while fetoscopy followed by placentesis caused a mean delta AFP of 462.8 ng/ml (represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…MSAFP was found to rise over 40 per cent in 76 per cent of the patients; however, the actual amount of calculated FMB is less than 0.1 ml. The chance of Rh isoimmunization with this small amount of FMB is 3 per cent (Zipursky and Israels, 1967). Therefore, 50 pg of Anti D IgG may be sufficient to avoid maternal isoimmunization and the possibility of enhancement in an Rh negative mother.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…MSAFP was found to rise over 40 per cent in 76 per cent of the patients; however, the actual amount of calculated FMB is less than 0.1 ml. The chance of Rh isoimmunization with this small amount of FMB is 3 per cent (Zipursky and Israels, 1967). Therefore, 50 pg of Anti D IgG may be sufficient to avoid maternal isoimmunization and the possibility of enhancement in an Rh negative mother.…”
Section: Resultsmentioning
confidence: 97%
“…To evaluate FMB related to genetic amniocentesis, the Kleihauer-Betke (KB) test and maternal serum determination of alpha-fetoprotein (AFP) have been advocated (Simpson et al, 1984;Horacek et al, 1976;Leleet al, 1982). Leleet al (1982) have found the latter to be a more sensitive indicator of FMB.…”
Section: Introductionmentioning
confidence: 99%
“…Fetomaternal hemorrhage (FMH) has been investigated after amniocentesis [1][2][3][4][5][6][7][8][9], fetoscopy and placentesis [10,11] and also after cordocentesis [12][13][14]. Fetomaternal bleeding following fetal sampling techniques is not rare and has been currently detected by either maternal serum ·-fetoprotein measurement, or the Kleihauer-Betke staining technique.…”
Section: Introductionmentioning
confidence: 99%